STRATEGIES TO REDUCE EMPLOYEE TURNOVER IN MSMES IN MUNA REGENCY - Ramiu, La Ode; Mokodompit, Eliyanti Agus (Penelitian dan Pengembangan Ilmu, 2024)
Employee turnover in SMEs is a significant challenge faced by the small and medium-sized business sector, particularly in underdeveloped regions. In Muna Regency, employee turnover in SMEs has been increasing due to factors such as low wages and limited career development opportunities. While several studies have been conducted in large corporations, research related to turnover in SMEs, especially in this region, is still very limited. This study employs a descriptive qualitative approach with in-depth interviews with business owners, employees, and related parties to identify the factors influencing turnover and strategies that can be applied to reduce it. The findings suggest that performance-based incentives, skill development through training, and creating a positive work environment are effective strategies to reduce employee turnover in SMEs in Muna Regency. The implications of this study indicate that more structured and professional human resource management strategies are needed to reduce turnover and enhance the competitiveness and sustainability of SMEs in the region.